Effect of blueberry intervention on endothelial function: a systematic review and meta-analysis - Deng, Bixin; Lei, Yupeng; Zhou, Ruixi; Ruan, Tiechao; Lu, Wenting; Ying, Junjie; Yue, Yan; Mu, Dezhi (Frontiers in Physiology, 2024)
Endothelial dysfunction indicates blood vessel injury and is a risk factor for cardiovascular diseases. Blueberry has been approved for its benefits on human health, especially on cardiovascular function. However, its effect on endothelial function remains unclear. We conducted a systematic review and meta-analysis to explore the impact of blueberries on endothelial function in adults. After searching PubMed, Web of Science, Embase, and the Cochrane Library, 16 studies were included in the systematic review, and 11 were used for the meta-analysis. Data associated with endothelial function were extracted and pooled as mean differences (MD) with 95% confidence intervals (CI). Blueberry consumption significantly improved flow-mediated dilation (FMD) by 1.50% (95% CI: 0.81, 2.20; I2 = 87%) and reactive hyperemia index (RHI) by 0.26 (95% CI: 0.09, 0.42; I2 = 72%). A significant decrease in diastolic blood pressure (DBP) was also observed (MD: